INFLUÊNCIA DA ORIGEM DOS GRÃOS DE KEFIR E DO TIPO DE LEITE NA PARÂMETROS DE QUALIDADE DOS PRODUTOS ELABORADOS - ALVES, Osrilene Afonso; DE CASTRO, Thiago Luis Aguayo; MASCARENHAS, Maria do Socorro; CARDOSO, Claudia Andrea Lima Cardoso (ANAIS DO ENIC, 2024)
-